KAJIAN BELIMBING WULUH (Averrhoa belimbi linn) SEBAGAI BAHAN PENGGUMPAL TAHU - Rokhaenah, Siti; Kusuma Dewi, Yohana Sutiknyawati; Hartanti, Lucky (Jurnal Sains Pertanian Equator, 2019)
ABSTRACTTofu is a traditional food consumed by many Indonesia as a high source of protein. It is delicious and cheap. It is a soft food product which is made from a soybean processing. It utilizes the nature of protein which coagulates if acidified. The star fruit which contains high citric acid (92,6-133,8) can be used as a tofu coagulant. The purpose of this research was to gain the optimal amount of the extract of wuluh star fruit to be used as a tofu coagulant. Thus, it could result in the best tofu in terms of its physiochemical and sensory characteristics. The best treatment was gained from 7% extrac of wuluh star fruit. The physiochemical characteristics of tofu had 48,21% of water content, 2,39mg/100 mg of vitamin C, 0,06kg/force level of solidity, and 13,88g/100g protein. Mean while, the result of test of preference were taste by 3,76 (dislike), texture by 3,68 (dislike), fragrance 4,08 (like), and color 4,12 (like).Keyword: wuluh star fruit, coagulant, tafu